A construção do medo no cinema à luz do estranho familiar: uma abordagem semiótica - Juaçaba, Helder Jaime (2011)
The study object of this thesis is the media support of cinema embodied in fiction film, whose construction is understood as a communicative function capable of generating meaningful effects. It more specifically refers to the identification of the forms used in film to produce sequences with the suggestive capacities to produce the effect of fear. In this context, emerged the research problem, as viewers already know it to be fiction. But why are the deliberate procedures in film construction able to generate the effect of fear? Therefore, the argument was developed that cinematographic procedures inserted certain language patterns, to touch on the uncanny collisions in the determinations of the unconsciousness of the viewer, causing the effect of fear. To support this argument, references to Das Unheimlich Freud's and Peirce's semiotic approach were used, in which fear could be evaluated as an interpretative sign in a logical order: the movie / cinema (sign) builds the stranger / Das Unheimliche (object) to produce the overall effect of fear on which the spectators must arrive (interpretant). The corpus includes the following films: Psycho (1960) - Director: Alfred Hitchcock, The shining (1980) - Director: Stanley Kubrick and The Others (2001) - Director: Alejandro Amenábar. Whose criterion of choice was the indisputable recognition and acceptance of the public and critical effects of tension, suspense, terror and fear in films. Beyond the intention of shedding new light on the interpretive films selected, the research aimed to contribute, by means of the semiotics and psychoanalysis, to expand the debate on one of the basic epistemological axes of the scientific field of communication: language